2016
DOI: 10.1111/mec.13921
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial ecology of lizards: insights into diversity in the wild, effects of captivity, variation across gut regions and transmission

Abstract: Animals maintain complex associations with a diverse microbiota living in their guts. Our understanding of the ecology of these associations is extremely limited in reptiles. Here, we report an in-depth study into the microbial ecology of gut communities in three syntopic and viviparous lizard species (two omnivores: Liolaemus parvus and Liolaemus ruibali and an herbivore: Phymaturus williamsi). Using 16S rRNA gene sequencing to inventory various bacterial communities, we elucidate four major findings: (i) clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
207
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(249 citation statements)
references
References 79 publications
35
207
7
Order By: Relevance
“…However, we found that stint were able to largely resist the incorporation of sediment micro‐organisms, despite high exposure through their feeding behaviour. This is in contrast to other studies that found relatively high levels of OTU sourcing (up to 45%) between the gut microbiota of resident species, including wild anoles and woodrats, and their ingested natural food (Kohl & Dearing, ; Kohl et al., ), although it is unknown whether hosts sourced these microbes as adults or juveniles. It is also in contrast to studies of migratory shorebird chicks on the breeding grounds, which have been shown to share nearly 40% of their gut bacteria with their environment between zero and 10 days old (Grond, ).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, we found that stint were able to largely resist the incorporation of sediment micro‐organisms, despite high exposure through their feeding behaviour. This is in contrast to other studies that found relatively high levels of OTU sourcing (up to 45%) between the gut microbiota of resident species, including wild anoles and woodrats, and their ingested natural food (Kohl & Dearing, ; Kohl et al., ), although it is unknown whether hosts sourced these microbes as adults or juveniles. It is also in contrast to studies of migratory shorebird chicks on the breeding grounds, which have been shown to share nearly 40% of their gut bacteria with their environment between zero and 10 days old (Grond, ).…”
Section: Discussioncontrasting
confidence: 96%
“…Moreover, laboratory rats challenged with the microbiota of other individuals develop a microbiota that is more diverse and resembles that of donor rats (Manichanh et al., ). Indeed, fully grown wild hosts have been shown to source a significant number of microbes from their environment, with wild woodrats and anole lizards estimated to source up to 25% and 47% of their gut microbiota community from ingested plant food, respectively (Kohl & Dearing, ; Kohl et al., ). Whether such high levels of microbial sourcing from the environment is characteristic of all wild hosts, including those with migratory lifestyles, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Relative abundance of the Firmicutes, however, was lower than expected in comparison with other studies of the reptilian gut microbiome [26,33,34]. Recent work by Abdelrhman et al, which to our knowledge is currently the only published culture-independent study to characterize gut microbial communities of live sea turtles, found much higher abundances of Firmicutes within captive loggerhead turtles [26].…”
Section: Discussionmentioning
confidence: 72%
“…Decreased microbial diversity and shifts in the species present have been reported for a number of the taxa, including but not limited to insects (Figure 1A), cnidarians (Figure 1B), lizards, fish, woodrats, and other mammals (Ley et al, 2008; Fraune et al, 2010; Wang et al, 2014; Kohl et al, 2014b, 2017; Mortzfeld et al, 2015; Clayton et al, 2016; Table 1). Therefore, defining the full diversity and functional traits of the microbiome with respect to the host would benefit from considering individuals in their native ecological niches to quantify if and how these differences shape the hologenome.…”
Section: Toward Nature's Laboratorymentioning
confidence: 81%